INCREASING PURCHASE INTENTION AND E-WOM USING THE ANTECEDENTS OF PARASOCIAL INTERACTION - Ramadhan Febratriantoro; Kurniawati Kurniawati; Yolanda Masnita (SEAN Institute, 2023)
The purpose of this study to examines the antecedents of parasocial interaction on purchase intention and e-WOM. This study tested a model that assesses parasocial interaction formed by social media influencer to increase purchase intention and e-WOM. Data were collected from 267 respondents who use social media and purchase coffee. Data analysis has been conducted using AMOS-Structural Equation Modelling (SEM). The result shows that there is a significant effect of social attractiveness on parasocial interaction, parasocial interaction on purchase intention and parasocial interaction on e-WOM. Another result shows that there is no significant effect of openness and interactivity on parasocial interaction. Among variable tested, the interactivity is the lowest. It indicates that social media influencer must upgrade their level of interactivity to their followers by creating a connection with their followers because the way social media influencer interact will make them feel important.